Pengembangan Inovasi UMKM Wong Djamoe Di Desa Pulosari Kabupaten Jombang - Mayga Putri Shabella; Yogi Pratama Putra; Diana Hertati; Taysa Adila (Cv. Utility Project Solution, 2023)
Jamu is a traditional drink which is one of the heritages, by utilizing spices that grow in Indonesia. This “Wong Djamoe” product is an innovative product of herbal medicine which is marketed in the form of yogurt and ice cream which has traditional herbal flavors such as ginger, kencur, turmeric, and temulawak flavors. However, in terms of MSME branding, this is a little lacking, namely the lack of identification from the production house and in terms of packaging. The general purpose of this community service activity carried out by UPN